Method analysis of accelerometers and gyroscopes in running gait: A systematic review - Norris, M.; Anderson, R.; Kenny, I. C. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2014)
To review articles utilising accelerometers and gyroscopes to measure running gait and assess various methodology utilised when doing so. To identify research- and coaching-orientated parameters which have been previously investigated and offer evidence based recommendations as to future methodology employed when investigating these parameters. Electronic databases were searched using key-related terminology such as accelerometer(s) and gyroscope(s) and/or running gait. Articles returned were then visually inspected and subjected to an inclusion and exclusion criteria after which citations were inspected for further relevance. A total of 38 articles were then included in the review. Accelerometers, gyroscopes plus combined units have been successfully utilised in the generation of research-orientated parameters such as head/tibial acceleration, vertical parameters and angular velocity and also coach-orientated parameters such as stride parameters and gait pattern. Placement of sensors closest to the area of interest along with the use of bi/tri- axial accelerometers appear to provide the most accurate results. Accelerometers and gyroscopes have proven to provide accurate and reliable results in running gait measurement. The temporal and spatial running parameters require sensor placement close to the area of interest and the use of bi/triaxial sensors. Post data analysis is critical for generating valid results.